Pengaruh Gestur Dan Kontak Mata Terhadap Kepercayaan Karyawan (Employee Trust) Pada Syntax Corporation Indonesia - Umam, Muhammad Khoirul; Abdurokhim, Abdurokhim; Nendi, Iksan; Askarno, Askarno; Opan Fadilah, Muhammad (Green Publisher Indonesia, 2025)
This research explores how eye contact and gestures influence employee trust levels at Syntax Corporation Indonesia. Employee trust plays a crucial role in various behaviors that impact productive working relationships. When trust is low, it can trigger conflicts and decrease productivity, whereas high trust can enhance motivation, performance, and employee loyalty. This study aims to fill the gap in existing research regarding the influence of nonverbal communication elements, particularly eye contact and gestures, on employee trust in the Indonesian workplace. Data were collected from 128 employees through a questionnaire and analyzed using multiple linear regression as a quantitative research method. The results indicate that both eye contact and gestures have a significant impact on employee trust, with eye contact having a greater effect. These findings emphasize the importance of nonverbal communication in creating a trustworthy environment and provide practical recommendations for management to enhance employee trust through the effective use of nonverbal cues.